Plant species identity and soil characteristics determine rhizosphere soil bacteria community composition in European temperate forests. Issue 6 (4th May 2019) - Ma, Shiyu; De Frenne, Pieter; Boon, Nico; Brunet, Jörg; Cousins, Sara A O; Decocq, Guillaume; Kolb, Annette; Lemke, Isa; Liira, Jaan; Naaf, Tobias; Orczewska, Anna; Plue, Jan; et al.
ABSTRACT: Soil bacteria and understorey plants interact and drive forest ecosystem functioning. Yet, knowledge about biotic and abiotic factors that affect the composition of the bacterial community in the rhizosphere of understorey plants is largely lacking. Here, we assessed the effects of plant species identity ( Milium effusum vs. Stachys sylvatica), rhizospheric soil characteristics, large-scale environmental conditions (temperature, precipitation and nitrogen (N) deposition), and land-use history (ancient vs. recent forests) on bacterial community composition in rhizosphere soil in temperate forests along a 1700 km latitudinal gradient in Europe. The dominant bacterial phyla in the rhizosphere soil of both plant species were Acidobacteria, Actinobacteria and Proteobacteria . Bacterial community composition differed significantly between the two plant species. Within plant species, soil chemistry was the most important factor determining soil bacterial community composition. More precisely, soil acidity correlated with the presence of multiple phyla, e.g. Acidobacteria (negatively), Chlamydiae (negatively) and Nitrospirae (positively), in both plant species. Large-scale environmental conditions were only important in S . sylvatica and land-use history was not important in either of the plant species. The observed role of understorey plant species identity and rhizosphere soil characteristics in determining soil bacterial community composition extends our understanding of plant-soil bacteria interactions in forest ecosystem functioning. Abstract : Rhizosphere soil bacterial community composition shows high habitat dependency. This study reported the influence of plant identity, soil chemistry, climate, nitrogen deposition and land-use history on its dynamics across Europe.